A Data‐Driven Epigenetic Characterization of Morning Fatigue Severity in Oncology Patients Receiving Chemotherapy: Associations With Epigenetic Age Acceleration, Blood Cell Types, and Expression‐Associated Methylation - Caroline Le; Maureen Lewis; Carolyn S. Harris; Liam Berger; Esther Chavez‐Iglesias; Lisa Morse; Anatol Sucher; Ritu Roy; Adam Olshen; Marilyn J. Hammer; Steve Paul; Margaret Wallhagen; et al. (Cancer Medicine)
ABSTRACT Background Moderate‐to‐severe fatigue commonly occurs in patients with cancer. Given the numerous roles that epigenetic processes may play in the development and severity of fatigue, the purposes of this study were to (1) use a data‐driven discovery approach to evaluate for mechanisms underlying morning fatigue in a group of oncology patients receiving chemotherapy and (2) identify common biological mechanisms associated with morning fatigue severity across these independent epigenetic evaluations. Methods Patients completed questionnaires during the week prior to their chemotherapy treatment. Severity of morning fatigue was evaluated using the Lee Fatigue Scale. Associations between morning fatigue severity and epigenetic aging acceleration (EAA), immune cell type compositions, and differential methylation of expression‐associated loci (eCpGs) in distal regions (i.e., upstream of a gene on the same chromosome) were evaluated. These results were then evaluated for common biological mechanisms. Results High morning fatigue was associated with older epigenetic age, positive EAA, and higher levels of EAA. Patients of the “Fast ager” type were more likely to have high morning fatigue. Higher morning fatigue was associated with lower (CD4 memory, CD8 memory, and NK) and higher (neutrophil and T regulatory) estimated proportions of cell types. Morning fatigue severity was associated with one differentially methylated distal region containing five eCpGs mapping to three genes (i.e., CILP, ONECUT1, SLCO3A1). Preliminary support was found for the role of Inflammaging as a common biological mechanism for morning fatigue. Conclusions This study provides an epigenetic characterization of morning fatigue in patients receiving chemotherapy. The findings suggest that biological aging, gene regulatory, and inflammatory processes may contribute to morning fatigue and provide future targets for therapeutic interventions.